Tramadol-induced anaphylaxis: a rare confirmed case - Ochmann, Anna; Glück, Joanna; Gawlik, Radosław (Alergologia Polska - Polish Journal of Allergology, 2025)
Tramadol is an opioid agonist that can be utilized for managing moderate chronic pain in adults. It is recognized for its safety and high tolerance. In comparison to other morphine-like drugs, it results in fewer adverse effects. Allergic reactions have been documented in several cases, though the occurrence was below 0.1%. The existing literature includes only a limited number of publications regarding documented hypersensitivity reactions following tramadol usage. We present the case of a 51-year-old woman with scoliosis and multilevel discopathy, who experienced two instances of anaphylactic shock: the first occurred following the use of an unidentified painkiller and the second happened after she took tramadol drops. In June 2024, she was admitted to our Allergology Unit with a suspected diagnosis of hypersensitivity to analgesic drugs. Given very low likelihood of anaphylaxis to tramadol, we chose to conduct an allergological evaluation that includes tramadol and other synthetic opioids.